Back to the Origin: In Situ Studies Are Needed to Understand Selection during Crop Diversification - Chen, Yolanda H.; Shapiro, Lori R.; Benrey, Betty; Cibrián-Jaramillo, Angélica (Frontiers in Ecology and Evolution, 2017)
Crop domestication has been embraced as a model system to study the genetics of plant evolution. Yet, the role of the environment, including biotic forces such as microbial and insect communities, in contributing to crop phenotypes under domestication and diversification has been poorly explored. In particular, there has been limited progress in understanding how human selection, agricultural cultivation (soil disturbance, fertilization, and irrigation), and biotic forces act as selective pressures on crop phenotypes. For example, geographically-structured pathogenic, pestiferous, and mutualistic interactions with crop plants have likely given rise to landraces that interact differently with local microbial and insect communities. In order to understand the adaptive role of crop traits, we argue that more studies should be conducted in the geographic centers of origin to test hypotheses on how abiotic, biotic, and human selective forces have shaped the phenotypes of domesticated plants during crop domestication and subsequent diversification into landraces. In these centers of origin, locally endemic species associated with wild ancestors have likely contributed to the selection on plant phenotypes. We address a range of questions that can only be studied in the geographic center of crop origin, placing emphasis on Mesoamerican polyculture systems, and highlight the significance of in situ studies for increasing the sustainability of modern agricultural systems.